Determinan investasi di Provinsi Jambi: pendekatan error correction model - Rio, Rio; Junaidi, Junaidi; Mustika, Candra (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
amount of export, global oil price, and electricity consumption on Jambi Province Investments in 1995-2021 using Error Correction Model (ECM) analysis method. The average rate of Domestic Investment contribution to the total investment in Jambi Province is 85,15% that is relatively high. Based in this research indicating that parcially rupiah exchange rate and export have a positif and significant effect on investment in a long term. Beside that in a short term rupiah exchange rate and electricity consumption have a positif and significant effect on Jambi Province investment. And global oil price has negatif and significant effect on Jambi Province investment.